Zuwanderungspolitik - ein neues kommunales Aufgabenfeld? - Kühn, Manfred; Münch, Sybille (Taylor & Francis, 2019)
The regulation of migration has mostly been regarded as a core task of the nation-state, which has the right to control its territorial borders and issue entry visas and citizenships. In the field of urban research, cities and municipalities are therefore regarded as largely dependent on state "migration regimes". This special issue examines the central question of whether there is also a "local turn" in the field of immigration policy. The cities of Europe are dependent on immigration in order to stabilise their population figures; without immigration they would shrink. In most cases, urban policy is growth- and competition-oriented. Nevertheless, most cities have not yet developed explicit immigration strategies. Wherever this does occur, it is for the most part socially highly selective: many urban development concepts merely articulate the desire for the immigration of young and qualified workers. Many cities still rely on the influx of the "creative class" when competing with other municipalities. The immigration of refugees and asylum seekers, on the other hand, is often seen as a burden by the municipalities and is delegated to integration policy. Due to the dispersal of refugees and asylum seekers by the German state, cities have very little room for manoeuvre in terms of controlling the influx of these immigrant groups. Against this background, this conceptual introductory article examines two key questions: (i) Which migration policy options do cities have and how are they theorised? (ii) Which proactive strategies can cities develop for the purpose of targeted recruitment of immigrants?
Immigration Policy - A New Field of Activity for Cities?
Keywords: Bevölkerungsentwicklung; Zuwanderung; Kommunalaufgabe; Standortmarketing; Kommunale Integrationspolitik; Migrationspolitik; Städtewettbewerb